Researching into Chinese university students’ mental health in the post-pandemic era – problems and causes - Ning, Xuan; Luo, Xiaoyu; Guo, Sijia (Frontiers in Psychology, 2024)
Mental health challenges have still been widely pervasive among Chinese university students after the outbreak of the COVID-19 pandemic. This article aims to explore mental health challenges encountered by Chinese university students in the post-pandemic era and explain causes to these challenges using a qualitative approach.We conducted six focus group interviews with university students in Zhuhai, China, and altogether 61 students including 43 female students, and 18 male students participated in the study. Our results indicate that sleep difficulties, anxiety, and stress are the three primary mental health challenges experienced by students. Academic pressure, social influence including peer pressure and pursuit of social acceptance, and pandemic related policies and measures are the causes to the above mental health challenges. The results of this study will inform the development of mental health promotion, intervention, and education activities for university students to bolster their resilience and cope with mental health problems in the post-pandemic era.Meanwhile, our results could illuminate the services stakeholders provide to university students in the future.